2002
DOI: 10.2337/diabetes.51.7.2220
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a 3-Month Low-Intensity Endurance Training Program on Fat Oxidation and Acetyl-CoA Carboxylase-2 Expression

Abstract: Endurance training has been shown to increase fat oxidation both at rest and during exercise. However, most exercise training studies have been performed at high exercise intensity in well-trained athletes, and not much is known about the effect of a low-intensity training program on fat oxidation capacity in lean sedentary humans. Here, we examine the effect of 3-month lowintensity training program on total and intramuscular triglyceride (IMTG)-and/or VLDL-derived fat oxidation capacity and skeletal muscle mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
97
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 43 publications
15
97
0
2
Order By: Relevance
“…It should be noted that, in the trained state, the skeletal muscle relies less on the oxidation of plasma FFA but also uses intramuscular triglycerides and VLDL triglycerides as a source of energy. 38,18 In conclusion, our data show that short-term endurance training reduces baseline ASP levels. This reduction is accompanied by a diminished exercise-induced increase in NEFA.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…It should be noted that, in the trained state, the skeletal muscle relies less on the oxidation of plasma FFA but also uses intramuscular triglycerides and VLDL triglycerides as a source of energy. 38,18 In conclusion, our data show that short-term endurance training reduces baseline ASP levels. This reduction is accompanied by a diminished exercise-induced increase in NEFA.…”
Section: Discussionsupporting
confidence: 55%
“…[15][16][17][18] In a recent study, we showed that a 3-month low-intensity endurance training program in previously untrained, sedentary males improved fat oxidative capacity and lowered plasma triglyceride levels. 18 In the present study, we could not detect any changes in fat oxidative capacity at the whole body level, probably due to the shortterm nature of the present training program. However, we did find that the increase in plasma FFA levels during exercise was already diminished after 2 weeks of endurance training, indicating improved fatty acid handling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently termed these different IMTG pools as 'good' and 'bad' lipids, with the IMTG stored as an adaptation to ETr and continually utilised for energy production as the 'good lipids', while the stagnant IMTGs accumulated in the obese skeletal muscle as the 'bad lipids'. 9 Other adaptations to Etr, such as increases in the activity of antioxidant molecules (such as glutathione peroxidase (GPX) and superoxide dismutase (SOD)), 57 increases in the percentage of the highly oxidative and insulinsensitive type I muscle fibres 61,62 as well as the increases in the b-oxidation pathway, 63,64 would also assist with the reduced risk of lipid peroxidation and insulin resistance.…”
Section: Effects Of Exercise On Imtgs and Insulin Resistancementioning
confidence: 99%
“…Indeed, exercise training has been shown to increase TG m content in muscle from healthy individuals [11], suggesting that the presence of triacyglycerol in the myocyte is not always associated with insulin insensitivity. In addition, it has been reported that the capacity to oxidize TG m and/or VLDL-derived fatty acids is increased both at rest and during exercise following a 3-month low intensity (40% of VO 2 peak) training program, and that increased rates of TG m oxidation could be beneficial in the prevention/treatment of Type 2 diabetes [12]. However, to date the effects of exercise training on insulin sensitivity and muscle lipid status in Type 2 diabetic patients has not been determined.…”
mentioning
confidence: 99%